2022
DOI: 10.1073/pnas.2119032119
|View full text |Cite
|
Sign up to set email alerts
|

Origin of iodine preferential attack at sulfur in phosphorothioate and subsequent P-O or P-S bond dissociation

Abstract: Significance Iodine-induced cleavage is widely used for detecting bacterial DNA phosphorothioation in gel electrophoresis, deep sequencing, and single-molecule optical mapping. However, we lack quantitative understanding of the phosphorothioate DNA (PT-DNA) cleavage efficiency and the chemoselectivity of this method for determination of phosphorothioate vs. phosphate. Computational explorations now reveal why iodine selectively attacks at sulfur in phosphorothioate links but not at normal phosphates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…A recent study found that Tri-HCl buffer takes an active role in DNA cleavage ( Huang et al, 2022b ), so Tri-HCl buffer was selected to provide a positive reaction environment for DTAFP. Since Tris-HCl was a neutral and weakly basic buffer, the prepared aptasensor were tested in Tris-HCl buffer ranging from pH 7 to pH 9.5, Figure 5C observed that the DPV response signal reached a maximum at pH 7.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that Tri-HCl buffer takes an active role in DNA cleavage ( Huang et al, 2022b ), so Tri-HCl buffer was selected to provide a positive reaction environment for DTAFP. Since Tris-HCl was a neutral and weakly basic buffer, the prepared aptasensor were tested in Tris-HCl buffer ranging from pH 7 to pH 9.5, Figure 5C observed that the DPV response signal reached a maximum at pH 7.…”
Section: Resultsmentioning
confidence: 99%
“…Low-energy conformers were optimized with the dispersion-included ωB97X-D functional in Gaussian 16 with the 6–31+G­(d,p) basis set. , The prediction of reactive sites between the nucleophile and electrophile was studied by Hirshfeld charges, frontier molecular orbital (FMO) analysis, and Fukui functions (FFs). The details have been provided in previous works. The isosurface maps were produced according to the outputs from Multiwfn calculations . We used the SMD solvation model to optimize the structure and calculate the frequency, obtaining the Gibbs free energy at 298 K via the GoodVibes program , Intrinsic reaction coordinate (IRC) calculations were conducted to determine the transition states.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we built PBXI–CALB systems and carried out MD simulations to study the enzymatic degradation mechanisms. The prereaction state analysis , and noncovalent interaction (NCI) analysis , of PBXI–CALB were performed to reveal the origin of substrate preference (details of MD simulations and subsequent analyses are given in the Supporting Information). Isosurface maps were produced using the VMD 1.9.3 program and Multiwfn 3.7 software package …”
Section: Methodsmentioning
confidence: 99%